Magnetic Photoluminescent Nanoplatform Built from Large-Pore Mesoporous Silica - Yang, Fan; Skripka, Artiom; Tabatabaei, Maryam Sadat; Hong, Sung Hwa; Ren, Fuqiang; Huang, Yue; Oh, Jung Kwon; Martel, Sylvain; Liu, Xinyu; Vetrone, Fiorenzo; Ma, Dongling (Chemistry of materials, 2019)
Integrating multiple components to realize cancer diagnosis and therapy in a single theranostic nanoplatform has drawn considerable attention. Herein, a multifunctional theranostic nanoplatform (mSiO2@PbS/CdS-Fe3O4) was successfully fabricated by carefully designing thiol-modified large-pore mesoporous silica nanospheres (mSiO2), followed by coordination-driven embedding of Fe3O4 nanoparticles (NPs) and PbS/CdS quantum dots (QDs) inside. The excellent feature of near-infrared (NIR) excitation and NIR emission of PbS/CdS QDs enables deep-tissue photoluminescence imaging, which was demonstrated ex vivo with tissue as thick as 14 mm. Meanwhile, owing to the presence of superparamagnetic Fe3O4 NPs, mSiO2@PbS/CdS-Fe3O4 can be rapidly confined under an external magnetic field (MF), and exhibit a significantly high T 2 relaxivity in T 2-weighted magnetic resonance (MR) images in vivo. When mSiO2@PbS/CdS-Fe3O4 was exposed to external physical stimuli of MF and/or NIR laser, they produced strong local heating through magnetothermal/photothermal effects. Owing to the unique mesoporous structure of mSiO2@PbS/CdS-Fe3O4, doxorubicin (DOX) was readily loaded into them and the drug-release profile was subsequently evaluated under multistimuli (pH/MF/NIR). The release of DOX was significantly enhanced at lower pH, and higher temperatures caused by magnetothermal/photothermal effects. Our results pave the road toward developing a highly powerful nanoplatform for bimodal imaging (NIR deep-tissue photoluminescence and MR imaging), and simultaneously for integrating synergistic treatment capabilities of hyperthermia and pH/MF/NIR-responsive drug release.